Regional variation on the presentation of Alzheimer's disease patients in memory clinics within Europe: data from the ICTUS study - Hausner, Lucrezia; Frölich, Lutz; Gardette, Virginie; Reynish, Emma; Ousset, Pierre-Jean; Andrieu, Sandrine; Vellas, Bruno (Journal of Alzheimer's disease, 2010)
This study set out to describe the variations within Europe for Alzheimer's disease (AD) patients with regards to clinical and socio-demographic features, co-morbidities, drug treatment, and psychosocial care. 1,379 mild to moderate AD subjects from